The Role of Work-Life Balance in Improving The Performance of Generation Z Employees - Carolus, C.; Ginting, Sunardi (Manunggal Halim Jaya, 2026)
Failing to effectively manage and establish clear boundaries between work and home life priorities often leads to decreased employee performance. Therefore, a work-life balance is essential for every employee to achieve maximum work results. Therefore, an organization must effectively leverage this policy to achieve its goals sustainably. This study examines the relationship between work-life balance variables and employee self-efficacy and performance, with a particular focus on intervening factors among Gen Z employees in Pontianak City, Indonesia. This research aims to investigate and identify the impact of self-efficacy on the performance of Gen Z employees in coffee shops in Pontianak City, with work-life balance serving as an intervening variable. A total of 208 respondents completed the research questionnaire, with seven individuals excluded from the analysis due to incomplete responses. This study employed a quantitative approach and utilised snowball sampling. This study used WarpPLS to analyse data via mediation models. Research findings show that self-efficacy has a positive and significant relationship with employee performance. Findings related to the work-life balance variable have a significant contribution to employee performance. The correlation between self-efficacy variables mediated by work-life balance can have a significant impact on employee performance.